Pengaruh Komisaris Independen, dan Leverage Terhadap Agresivitas Pajak pada Perusahaan Manufaktur Sektor Industri Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2020 – 2024 - Reza Riki Maulana; Setya Pramono (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The Influence of Independent Commissioners, Liquidity, and Leverage on Tax Aggressiveness in Manufacturing Companies in the Food and Beverage Industry Sector Listed on the Indonesia Stock Exchange for the 2020-2024 Period. This study aims to find out and provide empirical evidence regarding the Influence of Independent Commissioners, Liquidity, and Leverage on Company Tax Aggressiveness in Manufacturing Companies in the Food and Beverage Industry Sector Listed on the Indonesia Stock Exchange for the 2020-2024 period. The number of samples in the study were 21 companies with a total of 63 research data obtained using purposive sampling method based on predetermined criteria. The data used is secondary data in the form of audited annual financial reports for the 2020-2024 period taken from the website www.idx.co.id. The data analysis technique used is descriptive statistics, assumption test, multiple linear regression analysis test and hypothesis testing. Based on the results that have been obtained, it is found that the Independent Commissioner and Liquidity have no effect on Tax Aggressiveness and the Leverage variable has an effect on Tax Aggressiveness.